THE STRENGTHS AND WEAKNESSES IN THE IMPLEMENTATION OF SCHOOL-BASED MANAGEMENT: A STAKEHOLDERS’ PERSPECTIVE - ALONZO , ELIZABETH H.; MARTIN, MATRONILLO M. (International Journal of Psychosocial Rehabilitation, 2020)
The study unravels the implementation of School-Based Management (SBM) in Alfonso Lista District 1 and 2, Division of Ifugao. The study employed the qualitative research method through in-depth interview among the participants of the study which also used transcription. This also used the triangulation in order to penetrate details and commentaries among the participants of the study. The strengths of the implementation of SBM in both districts are categorized in two discrete yet dominating themes: the value of cooperation and motivation; and the worth of collaboration and delegation. As regards the weaknesses, it includes the poor enactment of transparency and low value of support mechanism. As to the remedial measures, consultative meeting, administrative protocol and open communication and decision making as the heart of the organization were utilized. Furthermore, SBM acknowledges school heads as frontiers of its implementation and enforces stakeholders’ involvement as well.The administrators developed mechanisms to perform leadership tasks in order to employ good governance particularly on decision-making, planning and monitoring. These administrators have continuously integrated core values as the heart of managing the school. In terms of fiscal management, the administrators considered the critical effects of transparency and support among the teachers and stakeholders.Proper Monitoring and evaluation tool must b designed by the school head to identify the schools’ priorities and needs; proper technical assistance must be provided. Faculty staff and stakeholder’ development must be initiated in both 2 districts to reinforce the harmonious relationships among them.